Association of Shoulder Impingement Syndrome with BMI in Younger Adults with Reporting Shoulder Pain - Maryam, Haseeba; Enderyas, Enderyas; Islam, Farooq; Thakur, Asim (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: To find out the association of shoulder impingement syndrome with BMI in younger adults with reporting shoulder pain. Methodology: This analytical cross-sectional study was carried out involving 18 to 39 years of male and female. Data was collected from Gujarat city (City Hospital, Gujrat Hospital, and THQ Hospital). This study was completed in 4 months after approval of synopsis. And total 233 males and females were evaluated. 18 to 39 years of males and females and who are willing to participate were included. Using a self-administered questionnaire, data was collected on demographic information (age, gender, occupation, height, weight, and BMI), as well as information specific to shoulder impingement syndrome. Findings: Total patients were 233.There were 19 patients who were underweight overall or 8.2%.There were 12 underweight individuals with positive Neer's Test results, and their proportion was 9.0%.There were 7 underweight patients with negative Neer's Test results, and their proportion was 7.0%.75 patients were overall healthy, and their proportion was 32.2%.There were 28 healthy patients with positive Neer's Test results, and their proportion was 21.1%.The percentage of healthy patients with a negative Neer's Test was 47, or 47.0%.There were 93 patients overall who were overweight, making up 39.9% of the total.There were 58 overweight individuals with positive Neer's Test results, and their proportion was 43.6%.Neer's Test results for overweight individuals who were 35 and whose percentage was 35.0% were negative. A total of 46 patients were obese, making up 19.7% of the total.There were 35 obese individuals with positive Neer's Test results, and their proportion was 26.3%.There were 11 obese individuals with negative Neer's Test results, and their proportion was 11.0%. Conclusion: This study reveals that the prevalence of shoulder impingement is associated with overweight or obese patients. The ratio of shoulder impingement was high in females. My result was significant. Recommendations: For study, it is recommended to gather data from several cities so that the conclusions may be generalized. In order to prevent people from developing shoulder impingement, obesity risk factors should be addressed.